Prospective Five-Year Follow-Up of Patients with Schizophrenia Suspected with Parkinson’s Disease - Asako Yoritaka; Tetsuo Hayashi; Keiko Fusegi; Rie Inami; Nobutaka Hattori (Parkinson's Disease)
Objective. It is difficult to distinguish patients with schizophrenia with neuroleptic-induced parkinsonism (NIP) from those with existing idiopathic Parkinson’s disease when their striatal dopamine transporter uptake is reduced. There is a possibility of misdiagnosis of Parkinson’s disease in patients with schizophrenia as schizophrenia with NIP, which leads to inappropriate treatment. This prospective study aimed at determining the underlying pathophysiology using detailed clinical and psychological assessments. Methods. We enrolled six patients with schizophrenia who had parkinsonism and were diagnosed with Parkinson’s disease according to the Movement Disorder Society Clinical Diagnostic Criteria, except for the fifth absolute exclusion criteria. Results. Five patients had been treated with neuroleptics for 20 years. One patient refused treatment for schizophrenia. All patients had impaired cognitive function at enrolment, olfactory dysfunction, and constipation. All patients were treated with dopaminergic therapy, and their parkinsonism substantially improved; one woman in her 40s experienced a wearing-off effect and dyskinesia. The uptake of dopamine transporter in the striatum decreased by 13%/year during the study period. Conclusion. Some patients with schizophrenia and parkinsonism benefit from dopaminergic therapy. Some of these patients may also exhibit Lewy pathology.